2017
DOI: 10.3802/jgo.2017.28.e50
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the PCR-reverse dot blot human papillomavirus genotyping test in cervical lesions from Chinese women in the Fujian province: a hospital-based population study

Abstract: ObjectiveTo determine the clinical significance of the polymerase chain reaction (PCR)-reverse dot blot (RDB) human papillomavirus (HPV) genotyping assay in cervical cancer screening.MethodsA total of 10,442 women attending the Fujian Provincial Maternity and Children's Health Hospital were evaluated using the liquid-based cytology (thinprep cytologic test [TCT]) and the PCR-RDB HPV test. Women with HPV infection and/or abnormal cytology were referred for colposcopy and biopsy. For HPV DNA sequencing, 120 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 30 publications
8
72
1
Order By: Relevance
“… 7 In our previous study, HPV-16 was the most prevalent genotype in the HR-HPV-positive women, followed by, from highest to lowest, HPV-52, -58, -18, -53, -33, -51, -56, -59, -68, -31, -66, -39, -35, and -45. 29 The data implied that the A9 pool (HPV-16, -31, -33, -35, -52, and -58) involved approximately 77% HPV positive genotypes and were the major HPV group in CIN2+ cases, compared to the A7 pool (HPV-18, -39, -45, and -59) at 14% and the A5/A6 pool (HPV-51, -56, and -66) at 6%. Based on the A9 pool, which is a major species in Fujian, we also evaluated HR-HPV primary screening for A9 pool as a triage approach to explore the Cervista test role in a primary screen.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“… 7 In our previous study, HPV-16 was the most prevalent genotype in the HR-HPV-positive women, followed by, from highest to lowest, HPV-52, -58, -18, -53, -33, -51, -56, -59, -68, -31, -66, -39, -35, and -45. 29 The data implied that the A9 pool (HPV-16, -31, -33, -35, -52, and -58) involved approximately 77% HPV positive genotypes and were the major HPV group in CIN2+ cases, compared to the A7 pool (HPV-18, -39, -45, and -59) at 14% and the A5/A6 pool (HPV-51, -56, and -66) at 6%. Based on the A9 pool, which is a major species in Fujian, we also evaluated HR-HPV primary screening for A9 pool as a triage approach to explore the Cervista test role in a primary screen.…”
Section: Discussionmentioning
confidence: 94%
“…The clinical performance characteristics of PCR-reverse dot blot (PCR-RDB) assays among 10,442 women in FCLSCs were evaluated previously; the results suggested that PCR-RDB can provide a reliable and sensitive clinical reference for cervical cancer screening. 29 In the current study, patient data were derived from that for FCLSCs using the Cervista test since 2012; moreover, the population eligible for this cohort study involved two arms, one consisting of healthy patients undergoing routine physical examinations, and another consisting of patients visiting the outpatient clinic for any gynecologic conditions except cancer. The total infection rate of HR-HPV tested using the Cervista HR-HPV test was estimated at 16.49%, which is in accordance to our previous report 29 and other epidemiological studies regarding HPV in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the above methods are inconvenient and may cause large economic burden, which is not suitable for resource-limited countries. In our previous study, 8 stated that the PCR-RDB HPV genotyping test could be applied in cervical cancer primary screening for hospitalbased opportunistic screening. However, there is no adequate research on whether the PCR-RDB HPV test is suitable for the posttreatment of high-grade cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous population-based screening results have demonstrated that the overall prevalence of hrHPV varies from 9.9-27.5% across China [22]. A previous study suggested possible reasons for this inconsistency, such as, different study populations, geographical prevalence, and differences in detection methods [23]. The HPV GenoArray test was a PCR-based kit that detected individual HPV genotypes.…”
Section: Discussionmentioning
confidence: 99%